Penyuluhan Fiqih Munakahat Sebagai Upaya Membangun Harmoni Dalam Rumah Tangga di Desa Danau Redan Kecamatan Teluk Pandan - Haika, Ratu; Prima, Anggra; Shodiqin, Imam; Amanda, Nadya Desri (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
This research aims to evaluate the effectiveness of munakahat fiqh counseling activities in increasing understanding and healthy practices in the field of marriage and family among the Muslim community in Danau Redan Village. This activity focuses on aspects of Islamic law and ethics relating to marriage and family life. The evaluation method involves assessments before and after the activity, as well as in-depth interviews with participants. Extension activities involve expert fiqh presenters, group discussions, and questions from participants to ensure in-depth understanding. The initial survey showed varying levels of understanding of the problem of hypocrisy among participants. After the outreach activities, the survey showed a significant increase in understanding, as well as positive changes in attitudes and behavior regarding marriage and family life. The results of this research provide insight into the success of munakahat fiqh counseling activities in increasing the understanding and application of Islamic values ​​related to marriage in the village. Implications for the development of similar activities in other places and suggestions for increasing the effectiveness of extension are also discussed in this research.